Oncogenic driver mutations, treatment, and EGFR-TKI resistance in a Caucasian population with non-small cell lung cancer: survival in clinical practice - Faehling, Martin; Volckmar, Anna-Lena; Stenzinger, Albrecht (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.20857 Martin Faehling, Birgit Schwenk, Sebastian Kramberg, Robert Eckert, Anna-Lena Volckmar, Albrecht Stenzinger, Jörn Sträter
Gesehen am 12.11.2018